Development of a wireless ultrasonic brain stimulation system for concurrent bilateral neuromodulation in freely moving rodents - Kim, Evgenii; Kum, Jeungeun; Lee, Seung Hyun; Kim, Hyungmin (Frontiers in Neuroscience, 2022)
Bilateral brain stimulation is an important modality used to investigate brain circuits and treat neurological conditions. Recently, low-intensity pulsed ultrasound (LIPUS) received significant attention as a novel non-invasive neurostimulation technique with high spatial specificity. Despite the growing interest, the typical ultrasound brain stimulation study, especially for small animals, is limited to a single target of sonication. The constraint is associated with the complexity and the cost of the hardware system required to achieve multi-regional sonication. This work presented the development of a low-cost LIPUS system with a pair of single-element ultrasound transducers to address the above problem. The system was built with a multicore processor with an RF amplifier circuit. In addition, LIPUS device was incorporated with a wireless module (bluetooth low energy) and powered by a single 3.7 V battery. As a result, we achieved an ultrasound transmission with a central frequency of 380 kHz and a peak-to-peak pressure of 480 kPa from each ultrasound transducer. The developed system was further applied to anesthetized rats to investigate the difference between uni- and bilateral stimulation. A significant difference in cortical power density extracted from electroencephalogram signals was observed between uni- and bilateral LIPUS stimulation. The developed device provides an affordable solution to investigate the effects of LIPUS on functional interhemispheric connection.